2019
DOI: 10.1111/1460-6984.12459
|View full text |Cite
|
Sign up to set email alerts
|

Speech and language therapists’ views on parents’ engagement in Parent–Child Interaction Therapy (PCIT)

Abstract: Background Parents’ play an essential role in Parent–Child Interaction Therapy (PCIT) as the primary agent of intervention with their child. Unfortunately, speech and language therapists (SLTs) report that parents’ engagement is challenging when conducting PCIT. Although focusing on and stimulating the engagement of parents, when needed, can increase the success of PCIT, little is known about what factors influence parent engagement. Aims To explore SLTs’ views about the factors that facilitate or pose barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…Research which has identified that incongruent expectations about how families will be involved may negatively affect engagement (Klatte et al . 2019, Skeat and Roddam 2019) further strengthen these recommendations. An ongoing need to negotiate roles throughout intervention has also been identified, and it has been suggested that SLPs should regularly ‘check in’ with families and ‘follow their lead’ regarding how they would like to be involved (Watts Pappas et al .…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Research which has identified that incongruent expectations about how families will be involved may negatively affect engagement (Klatte et al . 2019, Skeat and Roddam 2019) further strengthen these recommendations. An ongoing need to negotiate roles throughout intervention has also been identified, and it has been suggested that SLPs should regularly ‘check in’ with families and ‘follow their lead’ regarding how they would like to be involved (Watts Pappas et al .…”
Section: Discussionmentioning
confidence: 74%
“…A systematized review of existing research related to engagement (i.e., family investment and involvement) in early SLP intervention found that families become 'engaged' (i.e., ready and empowered to take an active role in intervention, both inside and outside sessions) as they work together with clinicians over time (Melvin et al 2019). Other studies have also revealed that there are multiple aspects that make up an understanding of engagement in this setting (e.g., Klatte et al 2019, Melvin et al 2020. In particular, Melvin et al (2020) conducted a study where Australian speech-language pathologists (SLPs) described characteristics of families they considered to be 'engaged' in early intervention.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations